ANALISIS BEBAN KERJA DAN JUMLAH PEKERJA DI BAGIAN GUDANG SPARE PART PADA PT. INDOFOOD CBP SUKSES MAKMUR TBK CABANG MEDAN - Rida , Rizkha; Yudisha, Nabila; Gunawan, Indra; Pramono (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2023)
In facing competition in the current era of globalization, one of the efforts made by the company is to increase the productivity of its employees. This study aims to analyze the workload of workers at PT. Indofood CBP Sukses Makmur Tbk Medan Branch in the spare part warehouse section. The workload analysis method with work sampling is used to collect work and idle data from employees in the spare part warehouse. From the calculation results, the workload in shift-1 is quite high, while in shift-2 and shift-3 it is still not high enough so that it can still be optimized. The proposed improvement is to shift some of the work in shift-3 to shift-2 and eliminate employees in shift-3 by turning on other employees whose work locations are closest and allow them to handle work in the spare parts warehouse in shift-3